Anggaran Belanja Daerah Berbasis Maqasid al Syari’ah: Analisis Realisasi Anggaran Kota Palopo - FIRMAN MUHAMMAD ARIF (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
This paper discusses about Regional shopping budget based maqasid al syari’ah: realization analysis of the palopo city budget with the focus of the problem, namely, the reality of empowering the government expenditure budget and realization of its utilization in Palopo City, how the government and its policies encourage the development of people’s living standards with the realization of the government expenditure budget in terms of the hierarchy or interconnectivity of the concept of maqasid al-syari’ah. The type of research is field research that is descriptive and explorative by using multi approaches such as normative, juridical, sociological, and welfare theology. The results showed that the local government was considered to have carried out various efforts and policies by encouraging the development of people’s lives. The realization of the government expenditure budget is considered to have interconnectivity with the concept of maqasid al syari’ah. Massive acceleration of budget absorption is carried out so that dependence from the central and provincial levels can be minimized. Assessment of the local government in budget management has reflected the government’s performance every year. The realization of these regional budget expenditures has a broad impact on the standard of living of the community, especially in the provision of better basic services for its citizens. There are pro-people policies that are protective, responsive, constructive and aspirational.